BASSHÍ MÁDENIYATÍ HÁM JUWAPKERSHILIGI - Bektursinova, G.J. (SCIENCE and SOCIETY, 2025)
This article discusses the issues of leadership culture and its responsibility. The author emphasizes that the leader’s personal culture, moral values, and management responsibility directly affect the success of the organization and the effectiveness of the team. The article also analyzes such aspects as the concept of leadership culture, the leader’s communicative skills, fair decision-making, and a responsible approach. The author substantiates the importance of a leader not only having professional knowledge and skills, but also adhering to ethical principles.